A Companion to David Foster Wallace Studies
XII, 250 p.
Keywords: Criticism of the work of David Foster Wallace has tended to be atomistic, focusing on a single aspect of individual works. A Companion to the Work of David Foster Wa ll ace is designed as a professional study of all of Wallace's creative work. This volume includes both thematic essays and focused examinations of each of his major works of fiction.